Religious Harmony and Improving The Community's Economy In Resin Plantations Pakel Village Lumajang - Ramadhani, Kurniawan; Marianingsih, Ita; Faizal, Ahmad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research aims to reveal how the values of local wisdom, especially in the context of religious harmony, contribute to the economic improvement of the resin plantation community in Pakel Village, Gucialit District, Lumajang Regency. Through a qualitative phenomenological approach, this study found that the harmony between religious communities in the village has given birth to a strong practice of mutual cooperation, which is reflected in the joint management of resin plantations. A work ethic that upholds justice and equality regardless of religious background has encouraged increased productivity and income of the community, especially for resin seekers. These findings show that local wisdom has great potential to become social capital in the economic development of natural resource-based communities